2019
DOI: 10.1177/1945892419868441
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Local Allergic Rhinitis in Japan

Abstract: Background The concept of local allergic rhinitis (LAR) has been advocated recently. Allergic rhinitis in Japan is characterized by house dust mites (HDMs) and Japanese cedar pollen (JCP). To investigate LAR in Japan, total IgE and antigen-specific IgE (sIgE) were measured in inferior turbinate mucosa and their relationships with skin test (ST) and nasal allergen provocation test (NAPT) and as well as serum IgE levels were examined. Methods Subjects were 50 rhinosinusitis patients for surgery. ST was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…15 Demographical differences might be attributable as a study group in China found a prevalence of LAR in only 7.7% of patients in a cohort of 195 individuals whilst Ishida et al recently published data suggesting a prevalence of LAR in 2 of 14 patients (14.3%) and HDM LAR in 5 of 21 (23.8%) in a study of 50 highly selected Japanese patients suffering from chronic rhinosinusitis. 16,17 Contrary to these conclusions others found no prevalence of nasal IgE in patients with nonallergic rhinitis. 18 Such discrepant data was obtained in selected populations of subjects suffering from rhinitis.…”
Section: Introductionmentioning
confidence: 85%
“…15 Demographical differences might be attributable as a study group in China found a prevalence of LAR in only 7.7% of patients in a cohort of 195 individuals whilst Ishida et al recently published data suggesting a prevalence of LAR in 2 of 14 patients (14.3%) and HDM LAR in 5 of 21 (23.8%) in a study of 50 highly selected Japanese patients suffering from chronic rhinosinusitis. 16,17 Contrary to these conclusions others found no prevalence of nasal IgE in patients with nonallergic rhinitis. 18 Such discrepant data was obtained in selected populations of subjects suffering from rhinitis.…”
Section: Introductionmentioning
confidence: 85%
“…However, allergic rhinitis and asthma are heterogeneous disorders with multiple immunological phenotypes, including a Th2/Th17 reaction 29,31,33–35 ; therefore, clinical linkage with psoriasis may be possible via the Th17 pathway 29 . It should also be noted that allergic rhinitis is a common disease among the Japanese population, with a prevalence of approximately 40% 36 . The low risk of allergic rhinoconjunctivitis, asthma, and obesity‐associated patients with GPP requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…29 It should also be noted that allergic rhinitis is a common disease among the Japanese population, with a prevalence of approximately 40%. 36 The low risk of allergic rhinoconjunctivitis, asthma, and obesity-associated patients with GPP requires further research.…”
Section: Events and Symptoms Associated With A Gpp Diagnosismentioning
confidence: 99%
“…In addition, allergic rhinitis may also contribute to lingual tonsil hypertrophy as suggested by Coban et al 14 Yet, establishing a diagnosis of allergic rhinitis may be elusive. This is underscored by Ishida et al 15 who identified that many patients undergoing surgery for CRS were identified to have elevated nasal antibodies to house dust mites and Japanese cedar pollen despite negative blood and skin allergy tests. The difficulty of identifying the underlying pathogenesis of CRS can also be perplexing.…”
mentioning
confidence: 99%
“…This is underscored by Ishida et al. 15 who identified that many patients undergoing surgery for CRS were identified to have elevated nasal antibodies to house dust mites and Japanese cedar pollen despite negative blood and skin allergy tests. The difficulty of identifying the underlying pathogenesis of CRS can also be perplexing.…”
mentioning
confidence: 99%